Cone beam computed tomography findings in monostotic fibrous dysplasia of the mandible: a case report - Restiti, Rr Dinar; Budhiana, Aries Sugih; Pramanik, Farina (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2025)
Objectives: This case report aims to describe the 3-dimensional radiographic features of Fibrous Dysplasia of the mandible. Case Report: A 38-year-old woman came to Padjadjaran University Dental Hospital with complaints of an enlarged right lower jaw, feeling hot, and a limited mouth opening of ±2cm. The patient was then referred for a CBCT (Cone-Beam Computed Tomography) examination. Conclusion: Based on the examination results, it was concluded that on CBCT (Cone Beam Computed Tomography) radiography, radiolucent lesions, ill-defined, bone-expanding lesions occurred in the facial bones. This case leads to a radiological diagnosis of suspected fibrous dysplasia.